A colorimetric method for quantitative visualization of diffusion and internal circulation in liquid–liquid two-phase flow. (15th February 2022) - Hirano, Hiroyuki; Tsuzaki, Shogo; Obata, Hideaki; Kihara, Tomohiko
Graphical abstract: Abstract: Herein, we propose a new method for the quantitative evaluation of mass-transfer characteristics in liquid–liquid two-phase flow during the formation of slug and its progression in a microchannel. The experimental setup included a 0.3-mm square microchannel with a Y junction. Distilled water with pH indicator and cyclohexane containing acetic acid were selected as the probe fluids. The acetic-acid concentrations were 0.05 and 0.1 vol%, while the volumetric velocity of the aqueous and organic phases was 0.03 mL/min. Acetic-acid diffusion and its internal circulation in the aqueous slug were visualized by color changes and recorded as microscopically magnified video images. By adopting a deep-learning algorithm, the aqueous slugs were segmented, and a calibration method converted color information to acetic-acid concentration values. The experimental results were comparable with those of previous studies. The presented method also revealed several new features that could not have been observed quantitatively by established experimental methods.